ASTHMA AND INNOVATION: CHALLENGES AND OPPORTUNITIES IN DISEASE CONTROL - Antonio, Gabriela de Amorim Ferreira; Bueno, Jéssica Cristina Esmarjassi de Castro; Araujo , Maria Ester de Carvalho; Osório, Lara Fabia Leite; Fernandes, Isabelle de Paula; França, Melissa Maria Ramos; Morais , Lurdes Maria de (Editora Impacto Científico, 2025)
Asthma is a common chronic respiratory disease affecting millions of people and presents significant challenges in its control. The objective of this work was to analyze the relationship between asthma and innovative therapies, identifying challenges and opportunities in disease management. The research used as its initial methodology a literature review on the epidemiology, pathophysiology, and innovative treatments of asthma. Subsequently, a technical visit was made to the Research Center in Lorena – SP. The third phase of this work was the creation of the "Asthma Diary," a practical tool for monitoring symptoms, adherence to treatment, and communication between patients and healthcare professionals. The diary includes sections for recording crises, medical consultations, health history, and information about the disease, promoting more efficient and personalized care. Asthma is a complex and multifactorial condition, with significant challenges in Brazil, highlighting barriers such as restricted access to medications, misinformation, and limitations in healthcare systems. The research reinforces the importance of innovative and personalized strategies to address chronic public health problems and improve the quality of life of asthmatic patients. It is concluded that the "Asthma Diary" can be a practical solution to improve disease control, suggesting its implementation in a pilot program as an effective tool for managing the condition and adherence to treatment.DOI: https://doi.org/10.56238/edimpacto2025.091-022